Quantitative Ultrasonography Techniques for Assessing Femoropopliteal Atherosclerotic Lesions Using Peak Systolic Velocity Ratio: The TURN-UP Study II - Aiko Hayashi; Masahiko Fujihara; Mitsuyoshi Takahara; Yumiko Komiya; Shun Aoki; Mina Enoki; Takamitsu Miyauchi; Rika Tanimoto; Takashi Araki; Keisuke Ishida; Isao Suminoe; Masayuki Nakakura; et al. (Journal of Endovascular Therapy, 2026)
Purpose: Peak systolic velocity ratios (PSVRs) measured by duplex ultrasound (DUS) are commonly used to evaluate arterial stenosis in patients with lower extremity artery disease. However, standardized measurement protocols have not yet been established. Although guidelines recommend setting the angle correction to 60° or as low as possible below 60°, the optimal angle correction for accurate PSVR measurement remains unclear. This study aimed to determine the appropriate angle correction values. The primary endpoint was the intraclass correlation coefficients (ICCs) for inter-observer and intra-observer agreement in PSVR measurements. Results: The ICCs for inter-observer agreement for PSVR measurements were 0.65 (95% confidence interval = 0.32-0.75), 0.72 (0.40-0.79), and 0.74 (0.51-0.78), for angle correction values of 45°, 50°, and 60°, respectively. No significant differences were observed between the measurement methods. The ICCs for intra-observer agreement in PSVR measurements were 0.95 (95% confidence interval = 0.93-0.97), 0.97 (0.95-0.98), and 0.96 (0.95-0.97) when the angle correction values were set at 45°, 50°, and 60°, respectively. No significant differences were found between the measurement methods ( P = .12 for 45° vs 50°, P = .41 for 50° vs 60°, and P = .59 for 60° vs 45°). Conclusion: No significant differences were noted among the 3 angle correction values. Therefore, an angle correction value of 45° to 60°, tailored to the specific clinical context, is considered reasonable. Clinical Impact The optimal angle correction for peak systolic velocity ratio (PSVR) measurement has not been clearly established. This prospective multicenter study demonstrates that angle correction values between 45° and 60° provide comparable inter- and intra-observer reproducibility. These findings suggest that strict adherence to a single angle correction value may not be necessary in clinical practice. Instead, selecting an angle close to the actual angle of incidence within this range may improve feasibility without compromising measurement reliability. These results provide practical guidance for standardizing PSVR assessment in routine vascular ultrasound examinations and clinical research.